Influence of Workload on Turnover Intention and The Role Of Job Satisfaction As A Mediation Variable - Gemma Galgani Nirma; Pudjo Sugito; Boge Triatmanto; Rofikul Amin; Isman I (Business Management Research, 2025)
Human resources play an important role in improving the company's progress. One action to prevent employees from having turnover intentions is to pay attention to workload and job satisfaction. The aim of this research is to determine the effect of workload on turnover intention and the role of job satisfaction as a mediating variable for employees at PT X partially and simultaneously. The research carried out was research using quantitative methods. The research sample was determined using total sampling to obtain a sample of 50 respondents. The data collection technique used by researchers is a questionnaire. The data analysis method used is path analysis. The research results prove that 1). workload influences employee turnover intentions at PT X. 2). workload has no effect on employee job satisfaction at PT. X. 3) job satisfaction has no effect on turnover intention 4) job satisfaction has no effect on turnover intention which is mediated by job satisfaction. What leaders need to pay attention to is increasing job satisfaction by paying attention to employee workload and providing bonuses to support enthusiasm for work.